Nab-paclitaxel plus cisplatin versus gemcitabine plus cisplatin as first-line treatment in advanced biliary tract cancer: results of a multicentre, randomised, phase II trial - Xiao Yang; Yu-Hong Dai; Hui Peng; Ming-Sheng Zhang; Qiang Fu; Shun-Fang Liu; Li Sun; Yan-Mei Zou; Hai-Sheng Xu; Ping Qiu; Hong Qiu; Qiao Huang; et al. (BMC Cancer)
Abstract Background The efficacy and safety of conventional first-line chemotherapeutic regimens for the treatment of advanced biliary tract carcinomas (ABTCs) have been unsatisfactory. Objectives We aimed to explore alternative chemotherapeutic regimens capable of providing improved efficacy and fewer side-effects. Design Multicentre, randomised, phase II clinical trial. Methods Patients with unresectable advanced-stage tumors, or those who have developed recurrence or metastasis following initial radical surgery, between January 2021 and November 2022 were included. The participants were randomised to either a gemcitabine-cisplatin group (GC) or an albumin-paclitaxel-cisplatin group (NC). Progression-free survival (PFS) was the primary outcome, whereas overall survival (OS), and objective response rate (ORR) were the secondary outcomes. Results The trial enrolled 75 patients and had a median follow-up period of 11 months. The median PFS (mPFS) was 7.8 m (95% confidence interval [CI]: 5.4–14.0 m) in the NC group, and 7.0 m (95%CI: 3.9–10.1 m) in the GC group (p = 0.0034, hazard ratio [HR] = 0.5136, 95%CI: 0.3136–0.8411). Median OS for the NC group was 12.4 m (95%CI: 7.3–22.3 m) and for the GC group was 12.1 m (95%CI: 6.7–20.7 m), with no significant differences (p = 0.4592, HR = 0.811, 95%CI: 0.463–1.442). PFS rates at 6 and 8 months were 52.6% vs. 73.0% and 13.2% vs. 35.1% for the NC and the GC group, respectively (p < 0.05). As the secondary endpoint, ORR rates, there was no significant difference between the two groups. GC group had 13 (34.2%) patients achieved ORR, while NC group had 14 (37.8%). Regarding safety, In the context of thrombocytopenia, the incidence was significantly lower in the NC group compared to the GC group (27% vs 50%, P = 0.041). Conversely, with regard to sensory neuropathy, the NC group demonstrated a higher incidence (62.1% vs 36.8%, P = 0.028). Conclusion In this phase II non-inferiority trial, NC demonstrated comparable efficacy to GC in advanced BTC, with a trend toward improved PFS and a potentially favorable hematological toxicity profile. Further studies are warranted to confirm these findings in the context of a modern immunotherapy-based standard. Trial registration Clinical Trials.gov identifiers: NCT04692051. Registered October 31, 2018.  https://www.chictr.org.cn/showproj.html?proj=38440 .